Exploring Interconnection of Rural Female Learners' Psychological Resilience and Academic Achievement Amidst Climate Change in Zimbabwe - Munyaradzi, Chidarikire; Mweli, Patrick (Journal of Ecohumanism, 2025)
This qualitative study explored the intricate relationship between the psychological resilience of rural female learners and their academic achievement in the context of climate change in Zimbabwe. Focusing on two secondary schools in the Masvingo North region, the research employed a case study design to examine the lived experiences of 13 participants, including learners, educators, and community members. Despite the growing body of literature on climate change and education, a specific gap existed regarding the interplay between psychological resilience and academic performance among rural female learners in Zimbabwe. This study aimed to fill that gap by providing nuanced insights into how environmental challenges impacted learners' psychological well-being and educational outcomes. Through focus group discussions, the research captured authentic narratives, revealing that enhanced resilience led to improved academic performance among participants. Thematic analysis of the data highlighted critical patterns. One finding was that enhanced psychological resilience positively influenced academic performance among rural female learners facing climate change challenges. Therefore, it was recommended that stakeholders implement targeted resilience-building programs in rural schools to support female learners' academic achievements.